Intramolecular Forces Density in Mesophilic and Thermophilic Proteins: Amino Acid Clusters Based Study - Rukman Hertadi; Minoru Kanehisa (Jurnal Matematika & Sains, 2007)
Thermostability of (hyper)thermophilic enzymes has been taken as an advantage in industry to enhance biochemicalreactions at elevated temperature. Factors responsible for the thermostability in this class of proteins, however, stillremain unclear despite the many works that have been done to elucidate such factors by performing variouscomparative studies to homologous pairs of (hyper)thermophilic and mesophilic proteins. In the current work, weelucidated the factors by comparing intramolecular forces density in tertiary structure of mesophilic and(hyper)thermophilic proteins in terms of the content of various types of amino acid clusters. A graph spectral methodwas employed to probe the charged, hydrophobic and aromatic clusters in each tertiary structure of all classes ofthermophilic proteins used in our study. Our results revealed that mesophilic and (hyper)thermophilic proteins containsimilar level of all types of amino clusters, thereby stabilized with similar level of high-density intramolecular forces,but the former contain a higher number of non-cluster residues and less stabilized by electrostatic interactions, therebymore sensitive to heat.